Дисбиотические процессы в тканях полости рта крыс при экспериментальном сахарном диабете = Dysbiotic processes in rats oral cavity tissues in experimental diabetes mellitus - Stupak, E. P. (Journal of Education, Health and Sport, 2016)
Stupak E. P. Дисбиотические процессы в тканях полости рта крыс при экспериментальном сахарном диабете = Dysbiotic processes in rats oral cavity tissues in experimental diabetes mellitus. Journal of Education, Health and Sport. 2016;6(10):44-52. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159682 http://ojs.ukw.edu.pl/index.php/johs/article/view/3924 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 08.10.2016. УДК 616.731+612.045 ДИСБИОТИЧЕСКИЕ ПРОЦЕССЫ В ТКАНЯХ ПОЛОСТИ РТА КРЫС ПРИ ЭКСПЕРИМЕНТАЛЬНОМ САХАРНОМ ДИАБЕТЕ Е. П. Ступак ВГУУ «Украинская медицинская стоматологическая академия», г. Полтава Резюме Введение крысам аллоксана, протаминсульфата, сахарозы или липополисахарида вызывает развитие дисбиоза в тканях полости рта. Ключевые слова: сахарный диабет, гипергликемия, липополисахарид, дисбиоз, ротовая полость. Dysbiotic processes in rats oral cavity tissues in experimental diabetes mellitus E. P. Stupak HSEI «Ukrainian medical Stomatological Academy», Poltava Summary Aim: Determine the development of dysbiosis in the tissues of the oral cavity of rats with diabetes mellitus of the 1st, 2nd type, with a sugar load and under the influence of lipopolysaccharide (LPS). Materials and Methods: Diabetes type 1 was induced by alloxan (119 mg / kg, single dose), diabetes type 2 - using protamine sulphate (18 mg / kg / peritoneum within 10 days). Sugar load was conducted by the consumption of drinking water with sucrose (5%). Systemic endotoxemia was reproduced with LPS (6.6 mg / kg / intramuscularly, within 5 days). In the tissues of the oral cavity (cheek, tongue, gums) was determined urease and lysozyme activity, dysbiosis rate was calculated by the ratio of urease and lysozyme relative activities. Results: In diabetes of 1st and 2nd type under sugar load and after LPS administration in buccal mucosa and tongue is increased urease activity and reduced lysozyme activity, which leads to a significant increase in the degree of dysbiosis (in 7-27 times). Conclusion: Leading pathogenetic link of diabetes - dysbiosis may occur under the influence of hyperglycemia, and as a result of systemic endotoxemia. This circumstance dictates the need for anti dysbiotic prophylaxis and therapy of diabetogenic complications in the oral cavity tissues. Keywords: diabetes mellitus, hyperglycemia, lipopolysaccharide, dysbiosis, oral cavity.